(untitled) (Nigerian Journal of Physiological Sciences, 2024)
This study was designed to investigate the modulatory effect of ethanol root extract of Sarcocephalus latifolius (SL) on the fertility of hypertensive Wistar rats induced by Nw-Nitro-L-Arginine Methyl Ester. Fifty adult male Wistar rats were randomly divided into 5 groups A-E. The rats in group A (Control) were administered with distilled water while Groups B-E received L-NAME at 40 mg/kg, Groups C, D, were co-administered SL at dosage of 100 and 200 mg/kg body weight, respectively, and group E was co-administered with Captopril 20 mg/kg once daily for 28 days. L-NAME caused a significant increase in blood pressure (mmHg) with Systolic Blood Pressure (SBP) (159.08±2.89), Diastolic Blood Pressure (DBP) (114.67±3.83) and Mean Arterial Pressure (MAP) (120.90±4.65) values when compared with their respective control of (115.00±2.81, 80.91±2.76 and 91.9±2.68) in Group B. The high blood pressure was however lowered im groups co-administered with SL and Captopril. Higher morphological alterations of sperm cells were observed in hypertensive rats and hypertensive rats medicated with captopril in this study, It was noticed that the right testicular weight and right testicular length in group C were affected significantly when compared to the left testicular parameter in groups A and B. Semen characteristics showed a decrease in sperm motility and livability in hypertensive rats group compared to the control and extract treated groups. This decrease fell below acceptable 60 % minimum sperm motility recommended for breeding animals and percentage of the abnormal sperm cell in group B is higher than 20% maximum acceptable limit in normal breeding animals. Hypertension altered the reproductive indices in rats used for this study and could result in infertility but ethanol extract of S. latifolius ameliorated the reproductive organ damage in hypertensive rats. Keywords: Hypertension, Infertility, rats, Sarcocephalus latifolius, Nw-Nitro-L-Arginine Methyl Ester